Design of Social Media-Based Interactive Learning Media for Al-Islam and Muhammadiyah (AIK) Materials at Muhammadiyah Junior High School - Suryo Bayu Tirto Aji (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study aims to develop a social media-based learning platform, specifically an Instagram account (@AIK_Muh5), for Islamic Religious Education (AIK) at Muhammadiyah Junior High School, using the first two stages of the ADDIE model (Analysis and Design). The study is based on theoretical frameworks such as social media-based learning, the challenges of AIK in the 21st century, and educational theories like constructivism and connectivism. The platform is designed to offer interactive and engaging learning through visual content like infographics, educational videos, and Instagram’s interactive features (polls, stories, comments, and live sessions). This approach aims to enhance students' digital literacy, provide relevant content, and strengthen Islamic character. While the platform has potential, it faces limitations, including a lack of empirical data to measure its effectiveness, the risk of oversimplifying complex AIK material, and an unclear evaluation system. Additionally, access issues and age restrictions hinder its use. The study suggests continuous development, integration with face-to-face learning, and inclusive strategies to ensure equitable access for all students, positioning this platform as a model for AIK learning in the digital age.